Clinical utility of the SMSA grading tool for the management of colonic neoplastic lesions. Issue 5 (May 2017) - Sansone, Stefano; Ragunath, Krish; Bianco, Maria Antonia; Manguso, Francesco; Beg, Sabina; Bagewadi, Abhay; Din, Said; Rotondano, Gianluca
Abstract: Background: Whilst polyp size has been traditionally used as a predictor of the complexity of endoscopic resection, the influence of other factors is increasingly recognised. The SMSA grading system takes into account polyp Site, Morphology, Size and Access, with higher scores correlating with increased technical difficulty. Aims: To evaluate whether the SMSA grading tool correlates with endoscopic and clinical outcomes. Methods: This retrospective study was conducted at two high volume centres in the United Kingdom and Italy. All polyps identified at colonoscopy were included in this study and classified as per the SMSA grading system. Results: A total of 1668 lesions were resected in 1016 patients. There was a positive correlation between increasing SMSA level and the inability to resect lesions "en bloc" (p < 0.001). Histologically complete clearance was higher in the lower SMSA groups (p < 0.0001). Additional endoscopic therapies, were more commonly required with the higher SMSA groups to achieve histological clearance (p < 0.0001). Moreover, advanced histology in resection specimens and procedural complications were significantly less common in SMSA level 1 lesions compared to level 3 or 4 lesions (p < 0.0001). Conclusions: The SMSA grading tool is a useful predictor of outcome following the resection of colonic neoplastic lesions.